The influence of pH and fluid dynamics on the antibacterial efficacy of 45S5 Bioglass. (2nd February 2016) - Begum, Saima; Johnson, William E; Worthington, Tony; Martin, Richard A
Abstract: In recent years, there has been considerable interest in the potential antibacterial properties that bioactive glasses may possess. However, there have been several conflicting reports on the antibacterial efficacy of 45S5 Bioglass ® . Various mechanisms regarding its mode of action have been proposed, such as changes in the environmental pH, increased osmotic pressure, and 'needle-like' sharp glass debris which could potentially damage prokaryotic cell walls and thus inactivate bacteria. In this current study, a systematic investigation was undertaken on the antibacterial efficacy of 45S5 Bioglass ® on Escherichia coli NCTC 10538 and Staphylococcus aureus ATCO 6538 under a range of clinically relevant scenarios including varying Bioglass ® concentration, direct and indirect contact between Bioglass ® and microorganisms, static and shaking incubation conditions, elevated and neutralised pH environments. The results demonstrated that, under elevated pH conditions, Bioglass ® particles have no antibacterial effect on S. aureus while a concentration dependent antibacterial effect against E. coli was observed. However, the antibacterial activity ceased when the pH of the media was neutralised. The results of this current study, therefore, suggest that the mechanism of antibacterial activity of Bioglass ® is associated with changes in the environmental pH; an environment that is less likely to occur in vivo due to buffering of the system.